2022
DOI: 10.3390/ijms23020863
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Transcriptome Profiles of Human Amnion-Derived Mesenchymal Stromal/Stem Cells Induced by Three-Dimensional Culture: A Potential Priming Strategy to Improve Their Properties

Abstract: Mesenchymal stromal/stem cells (MSCs) are believed to function in vivo as a homeostatic tool that shows therapeutic properties for tissue repair/regeneration. Conventionally, these cells are expanded in two-dimensional (2D) cultures, and, in that case, MSCs undergo genotypic/phenotypic changes resulting in a loss of their therapeutic capabilities. Moreover, several clinical trials using MSCs have shown controversial results with moderate/insufficient therapeutic responses. Different priming methods were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 80 publications
1
19
0
Order By: Relevance
“…Although the results of our study are in line with previous research suggesting the superior immunomodulatory effects of 3D MSCs over 2D MSCs [ 15 , 16 , 18 , 22 ], some previous studies reported contradictory results [ 19 , 37 ]. In one study, T cell-suppressive abilities of MSCs were observed only in 2D MSCs and not in 3D MSCs; in that study, the T cell-suppressive abilities of 3D MSCs were partly restored by addition of a corticosteroid [ 37 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the results of our study are in line with previous research suggesting the superior immunomodulatory effects of 3D MSCs over 2D MSCs [ 15 , 16 , 18 , 22 ], some previous studies reported contradictory results [ 19 , 37 ]. In one study, T cell-suppressive abilities of MSCs were observed only in 2D MSCs and not in 3D MSCs; in that study, the T cell-suppressive abilities of 3D MSCs were partly restored by addition of a corticosteroid [ 37 ].…”
Section: Discussionsupporting
confidence: 90%
“…In addition to the changes in gene expression profiles such as the expression of genes with cell stemness and migration ability in 3D MSCs, EV production increases with the three-dimensional culture method, and the resulting EVs can have a cargo profile that is different from 2D MSCs [ 17 ]. In a recent study, total RNA sequencing using next-generation sequencing platforms on human amnion-derived 2D and 3D MSCs revealed profound transcriptome changes, including enhanced secretion of C-C motif chemokine ligand 2 (CCL2), C-X-C motif chemokine ligand 12 (CXCL12), and bone morphogenetic protein 2 (BMP2), which could contribute to a microenvironment favouring polarization of macrophages into the M2 phenotype [ 18 ]. However, a previous study conducted in an animal model of bleomycin-induced lung fibrosis suggested that EVs produced from 3D MSCs did not demonstrate enhanced immunomodulatory properties compared with 2D MSC-derived EVs [ 19 ], indicating that optimization of 3D MSC-derived EVs in each disease model is required.…”
Section: Introductionmentioning
confidence: 99%
“…A suitable approach to improving EVLP technique consists of using mesenchymal stromal/stem cells (MSCs) and/or their secretome, which contains extracellular vesicles (EVs, such as exosomes and EXOs) and other bioactive molecules, including cytokines, chemokines, growth factors, angiogenic and immunomodulatory factors [ 18 , 19 , 20 , 21 ]. Although the mechanisms are not fully defined yet, it has been widely demonstrated in both preclinical and clinical studies that therapeutic effects of MSCs are mediated, at least in part, by paracrine factors [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have clearly demonstrated that different methods of pre-conditioning are related to the type of cell population or biological process that need to be targeted [ 30 , 48 , 49 , 50 ]. For instance, our group recently demonstrated via transcriptome analysis that hAMSCs pre-conditioning modulates an extensive number of genes associated with regenerative processes and signaling pathways [ 51 ]. Thus, the identification of bioactive factors in the pre-conditioned CM from MSCs is crucial for the definition of strategies to stimulate tissue repair.…”
Section: Discussionmentioning
confidence: 99%